History and geography of human genetic diversity II - Cavalli-Sforza, Luigi Luca (Henry Stewart Talks, 2007)
Genetic markers inherited from a single parent, Mutational history of the Y chromosome (NRY), Genealogies of Y chromosome and mitochondria, Of Adam and Eve, Primates and Homo sapiens, Neanderthal and the spread of modern humans from East Africa, The spread of modern humans according to Y chromosome, Areas of origin of agriculture and animal breeding, Spread of cultivated wheat to Europe in the Neolithic period, Geographic maps of the first three principal components of Europe, Coevolution and hitchhiking of commensals: Helicobacter pylori, Coevolution of humans and cattle